Research design : creating robust approaches for the social sciences - Gorard, Stephen (London ; Thousand Oaks, Calif. : SAGE, 2013)
"Research design is of critical importance in social research, despite its relative neglect in many methods resources. Early consideration of design in relation to research questions leads to the elimination or diminution of threats to eventual research claims, by encouraging internal validity and substantially reducing the number of alternative explanations for any finite number of research 'observations'. This new book: discusses the nature of design; gives an introduction to design notation; offers a flexible approach to new designs; looks at a range of standard design models; and presents craft tips for real-life problems and compromises. Most importantly, it provides the rationale for preferring one design over another within any given context. Each section is illustrated with case studies of real work and concludes with suggested readings and topics for discussion in seminars and workshops, making it an ideal textbook for postgraduate research methods courses. Based on the author's teaching on the ESRC Doctoral Training Centre "Masters in Research Methods" at the University of Birmingham, and his ongoing work for the ESRC Researcher Development Initiative, this is an essential text for postgraduate researchers and academics. There is no book like Research Design on the market that addresses all of these issues in an easy to comprehend style, for those who want to design research and make critical judgements about the designs of others."--Publisher's website.
Part 1: Introduction. 'Design as distinct from methods. What Is Research Design? ; Introducing Designs in the Cycle of Research. -- Part 2: The preliminaries of research design. Identifying Researchable Questions ; Warranting Research Claims ; The Nature of Causal Claims. -- Part 3: Putting it all together. Identifying the Sample or Cases ; Comparing for Comparative Claims ; Matters of Timing and Sequence ; Evaluating Controlled Interventions. -- Part 4: More advanced considerations. Further Designs for Evaluation ; Challenges for Validity ; How Big Is a Difference? ; A Second Principle of Ethics. -- Part: Conclusion. Revisiting the Need for Robust Design.
Includes bibliographical references and index.
Keywords: Social sciences -- Research -- Design; Social sciences -- Research -- Design -- Case studies; Social sciences -- Research -- Methodology; Social sciences -- Research -- Methodology -- Case studies